Spatio-temporal analysis of the occurrence of human visceral leishmaniasis in Araçatuba, State of São Paulo, Brazil - Bermudi,Patricia Marques Moralejo (2018)
Abstract INTRODUCTION: This study aimed to describe the occurrence of human visceral leishmaniasis in Araçatuba with regard to time and space and to identify high risk areas. METHODS: We included all human visceral leishmaniasis autochthonous cases reported between 1999 and 2015. The incidence rates were calculated by sex, age, and year. The human visceral leishmaniasis cases were geocoded and grouped by urban census tracts, enabling the calculation of the incidence and mortality rates by census tracts. For the identification of high risk areas, we utilized the scan statistics and univariate Ripley’s K-function. RESULTS: The incidence presented a cyclic pattern in 1999-2009, with peaks in 2002 and 2007 (30.1 and 19.6 cases per 100,000 inhabitant-years, respectively). In 2010-2015, the incidence remained relatively stable with about 2.0 cases per 100,000 inhabitant-years. The scan statistics detected two spatial clusters of high risk and three spatio-temporal clusters of high risk that lasted from 2001 to 2008. A spatial autocorrelation was observed in the human visceral leishmaniasis case point distribution in 1999-2009. No spatio-temporal clusters and no spatial autocorrelation in the case point pattern were identified in 2010-2015. CONCLUSION: We identified a changing pattern of human visceral leishmaniasis occurrence in Araçatuba: the first period (1999-2009) showed a cyclic pattern, clusters, and presence of spatial dependence in the case point distribution; the second period (2010-2015) showed the lowest rates of all historical series, stable incidence, and cases with a random distribution pattern.